Using Picture Storybooks to Improve Children's Reading Skills - Trisnawati, Dewi; Pradana, Pascalian Hadi; Ali , A. Zulkarnain (Jurnal Amal Pendidikan, 2024)
The aim of this research is to determine the increase in children's interest in reading through the using picture story books. Classroom Action Research (PTK) is a research approach carried out by teachers in their own classes with the aim of understanding, improving, and developing the learning process and student learning outcomes. This method emphasizes the active participation of teachers as researchers in finding solutions to concrete problems that arise in the classroom. In cycle 1, it can be seen that a result of 44.4% was in the success category. This value shows that it does not meet the target indicator of success that has been determined, namely that at least 80% of children are able to observe the picture and answer the specified picture. Therefore, it is necessary to continue in the next cycle, namely the second cycle with two meetings. In cycle II, there was a significant increase in children's reading interest scores through picture book reading activities. The second cycle resulted in 6 children getting a score with the criteria of developing very well, 11 children getting a score with the criteria of developing as expected, and 1 child getting a score with the criteria of starting to develop. This shows that there are 17 children, or 94.4%, who have met the criteria for completion or indicators of research success. This shows an increase from cycle I, namely 44.4%, to 94.4% in cycle II..